PENGARUH MARKET TIMING DAN STOCK SELECTION TERHADAP KINERJA REKSA DANA DI INDONESIA (Studi Kasus Pada Reksa Dana Saham Periode 2013-2015) - Uun Indrawati; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to determine the effect of market timing (X1) and stock selection (X2) variables on mutual fund performance (Y). To measure market timing and stock selection variables using the Treynor-Mazuy model. While to measure the performance of mutual funds also use the model Treynor-Mazuy. Population in this research is conventional equity fund year 2013-2015 amounted 24 company. The sample in this study using purposive sampling technique amounted to 15 companies. Method of data analysis used in research is multiple linear regression. The results of this study indicate that simultaneously market timing and stock selection have a significant effect on the performance of equity funds in Indonesia. While partial test, it is found that market timing has negative and significant effect on mutual fund performance (sig 0,004) and stock selection has significant positive effect on mutual fund performance (sig. 0,005).Keyword : Mutual Fund Performance, Market Timing, and Stock Selection